Model Efektivitas Pelatihan Front Desk Agent Pasca Pandemi: Konteks Hospitaliti - Indrayani, I Gusti Ayu Putu Wita; Widiantini, Ni Luh Putu Erin; I Made Sucipta, Adnyana (Journal of Hotel Management, 2024)
This study aimed to assess the effectiveness of Front Desk Agent training at AKB Hotel post pandemic. Primary data were gathered through interviews with Front Office Managers and Front Desk Agents, focusing on training experiences and Front Desk Agent profiles. Additionally, secondary data from online travel agents, reflecting guest complaints related to Front Desk Agent services, were considered. The research incorporated both qualitative data, derived from training interviews, and quantitative data, encompassing room occupancy rates, Front Desk Agent numbers, and guest complaints. Employing a qualitative descriptive analysis technique, the study followed Woods' theory, which outlines steps to assess training effectiveness: Reaction, Learning Process, Behavior Change, and Outcomes. Ten Front Desk Agents was chosen from a total of 13 individuals for this study. Findings revealed the ineffectiveness of Front Desk Agent training post pandemic at AKB Hotel, emphasizing the need for improved training scheduling. The study underscores the importance of addressing issues identified through a comprehensive analysis to enhance the overall efficiency of Front Desk Agent training in challenging circumstances.